Ocular biomechanics due to ground blast reinforcement. (November 2021) - Karimi, Alireza; Razaghi, Reza; Girkin, Christopher A.; Downs, J. Crawford
Highlights: The blast wave due to GBR reached the skull prior to the IED blast itself. The highest and lowest IOPs were observed at IED heights of 1.70 and 0 m. Similar IOPs were observed regardless of the IED height from the ground (no GBR). GBR led to higher stresses and strains in the sclera. Results suggest the critical role of the GBR in head and ocular blast simulations. Abstract: Background and objective: Bomb blast injuries exerts a shearing force on the air-tissue interfaces, causing devastating ocular injury from the blast wave. Improvised explosive devices (IEDs) are usually placed at different heights from the ground to induce more severe injury through ground blast reinforcement (GBR). However, there is still a lack of knowledge of the role of GBR and IED height from the ground on ocular biomechanics, and how they can affect the intraocular pressure (IOP) in the eye. This study aimed to estimate the IOP due to frontal IED explosion at different heights from the ground using a fluid-structure interaction model with and without GBR effects. Methods: A 2 kg IED was placed within 5 m of the victim at 5 different heights from the ground, including 0, 0.42, 0.85, 1.27, and 1.70 m. Two different blast formulations were used to simulate the IED explosion: (a) spherical airburst, with no amplification of the initial shock wave due to interaction with the ground-surface, and (b) hemispherical surface-burst, where the initial blast wave is immediately reflected and reinforced by the ground (GBR). Results: Results revealed that the blast wave due to GBR reaches to the skull prior to the IED blast itself. The GBR also reached to the skull ∼ 0.6 ms earlier when the IED was on the ground compared to the height of 1.70 m. The highest and lowest IOPs of ∼ 17, 000 and ∼ 15, 000 mmHg were observed at the IED heights of 1.70 and 0 m from the ground considering GBR. However, when the role of the GBR is ignored, IOP of ∼ 9, 000 mmHg was observed regardless of the IED height from the ground. The deformation in the apex of the cornea was higher when considering the GBR (∼ 0.75 cm) versus no GBR (∼ 0.65 cm). Considering GBR led to higher stresses and strains in the sclera. Conclusions: When the role of GBR was ignored, the results showed similar patterns and magnitudes of stresses and deformations in the skull and eye regardless of the height of the IED from the ground, which was not the case when GBR was considered. The findings of this study suggest the critical role of GBR in ocular blast simulations.